PENGARUH PENERAPAN MODEL LEARNING CYCLE TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS XI IPS MAN GUNUNG PADANG PANJANG - Esi, Esi; Yenti, Isra Nurmai; Rizal, Yusmet (Jurnal Pembelajaran MIPA, 2014)
The research aim to determine whether the ability of understanding mathematical concepts students on the application of the Learning Cycle is higher than the ability of students understanding of mathematical concepts in conventional learning in IPS XI MAN Gunung Padang Panjang. The research was quasi-experiment, and the research design Randomized Only Control Group Design. Research procedures are: preparation, execution and completion. The instrument used was a test essays. The hypothesis was tested with Mann-U Whitney test. Based on the research results, obtained an average ability students understanding of math concepts in the experimental class was 87.12, while the control class is 59.66 Hypothesis tests using the Mann- U Whitney obtained 3.96. That is, the test statistic Z = 3.96 is greater than the critical value = 1,645, so the research hypothesis is accepted. Thus, the ability of students understanding of mathematical concepts in the application of the Learning Cycle is higher than the ability understanding mathematical concepts students in conventional learning.Key words: Learning Cycle, understanding of math concepts